A report of genetics from a social system perspective - Arnold Cathalifaud, Marcelo (Acta Bioethica, 2002)
In this article social system theory was applied in order to analyze the repercussions of bioscientific applications in contemporary society, and furthermore in order to explain the risk status of a habitual means of communication. From this perspective, genetic research is treated as an emerging problem one, which is self-made, that aims at situations which Latin American society has only just recently begun to face. The objectives of this study were to relate, from an observation of the second order, reports that were from genetically modified foodstuffs to the expectations generated by genetics research. Finally, this article indicates that the complexity is raised in social operations which will involve communication in genetics, communication that will guide its evolution, as is the case with communication in Bioethics.